Regulation of cerebral cortical neurogenesis by the Pax6 transcription factor - Manuel, Martine N.; Mi, Da; Mason, John O.; Price, David J. (Frontiers in Cellular Neuroscience, 2015)
Understanding brain development remains a major challenge at the heart of understanding what makes us human. The neocortex, in evolutionary terms the newest part of the cerebral cortex, is the seat of higher cognitive functions. Its normal development requires the production, positioning and appropriate interconnection of very large numbers of both excitatory and inhibitory neurons. Pax6 is one of a relatively small group of transcription factors that exert high-level control of cortical development, and whose mutation or deletion from developing embryos causes major brain defects and a wide range of neurodevelopmental disorders. Pax6 is very highly conserved between primate and non-primate species, is expressed in a gradient throughout the developing cortex and is essential for normal corticogenesis. Our understanding of Pax6’s functions and the cellular processes that it regulates during mammalian cortical development has significantly advanced in the last decade, owing to the combined application of genetic and biochemical analyses. Here we review the functional importance of Pax6 in regulating cortical progenitor proliferation, neurogenesis, and formation of cortical layers and highlight important differences between rodents and primates. We also review the pathological effects of PAX6 mutations in human neurodevelopmental disorders. Finally, we discuss some aspects of Pax6’s molecular actions including its own complex transcriptional regulation, the distinct molecular functions of its splice variants and some of Pax6’s known direct targets which mediate its actions during cortical development.